Rancang Bangun Cetakan Seal Apar Diameter 32.60 MM - Hanif Akbar, Ikhlasul; Arifin, Fatahul; Arnoldi, Dwi (Politeknik Negeri Sriwijaya, Indonesia, 2023)
This study aims to make a rubber-based fire seal with a diameter of 32.60 mm using a Compression Molding tool. Compression Molding itself is a set of printing tools by heating and pressing. The scheme of the basic processes consists of heating a charge (thermostat and reinforcement) to a certain temperature, in the mold cavity and then pressing it with a certain pressure.The first process begins with tool preparation and mold making, then rubber is made into a 32.60mm diameter fire seal. After everything has been prepared, then cut the rubber into small pieces to meet the volume of the seal in the mold and put the rubber into the mold. Press the mold using a Â re using the thermostat. After completion, the measurement of seal shrinkage includes the inside diameter, outside diameter, and seal thickness and then compared with the mold size, so that conclusions can be drawn. The calculation is influenced by the density of the structure after the testing process.